Badminton injuries in elite athletes: A review of epidemiology and biomechanics - Pardiwala, D. N.; Subbiah, K.; Rao, N.; Modi, R. (Indian Journal of Orthopaedics, 2020)
Badminton is a popular sport in India and with multiple medal prospects will be closely followed at the Tokyo 2020 Olympics. Considered the fastest of the racquet sports, players require aerobic stamina, agility, strength, speed, and precision, besides requiring good motor coordination and complex racquet movements. Injuries in badminton are common despite it not being a contact sport, and include overuse injuries, and acute traumatic events. The game is physically challenging and demands complex repetitive upper and lower extremity movements with constant postural variations and poses a high risk of overuse injuries to both the appendicular and axial musculoskeletal systems. Badminton also necessitates short bursts of movement with sudden sharp changes in direction, which places players at risk of non-contact traumatic injuries to joints and muscle-tendon units. Preventing injuries and decreasing time away from training and competition are critical in an elite badminton player`s sporting career. This analytical review identifies the incidence, severity, and profile of badminton injuries in elite players, and discusses the biomechanical basis of these injuries.